Determinantes da evasão universitária e impacto no gasto público - Gama, Bruna Borges de Oliveira (2018)
One of the major problems experienced by higher education institutions is the high rates of university dropout rates. University dropout can be understood by the student leaving the institution before the course ends, this abandonment results in significant financial, social and academic losses. In addition to the fact that the dropping of the undergraduate course generates wastage of public resources. For this reason, they have become a matter of concern and of great importance in the academic context. For this reason, the objective of this research is to identify the determinants of university school dropout and the impact of this evasion on public spending at the Federal University of Uberlândia. For this, in the first moment, all the literature of this subject was analyzed in order to identify the main variables that can influence in the decision of the student to evade or not of the course of graduation. The data collection of this research was obtained through the application of questionnaires and these were elaborated based on the determinants of university avoidance according to the literature analyzed in the study. Data analysis was performed in two phases: descriptive statistics and multivariate statistics. The results of the research reveal that the variables that most influenced university dropout at the Federal University of Uberlândia were: institutional reasons, the choice of another course, the support of friends, discontent with the course and future profession, classroom, faculty, transportation to university and personal problems. With regard to the impact of university evasion on public spending, a triangulation of several data sources was carried out. The results of this research indicate that the economic losses of UFU due to university school dropout, for the analyzed period, are around R $ 1 billion. In the analyzed period 22340 students left the course before the end. In addition to economic losses, university school dropout, generates social losses. For the applicability of this study, we suggest to the Federal University of Uberlândia some intellectual solutions that may contribute to the reduction of evasion rates, such as: vocational orientation, special attention to incoming students, follow-up and support to students from the initial periods, services provided to the student community, etc. We hope that this study will contribute to the discussions on this topic of significant importance to higher education. As a technological product, a workshop was planned to be held in the second half of 2018.